Immuno-Gold Labelling if Mycoplasma iowae for Light Microscopy - Shareef, Jalal M. (Sulaimani Journal for Pure and Applied Sciences, 1999)
Mycoplasma iowae is an egg transmitted organism with serotypes previously known as I,J,K,N,Q and R. Some members of this group are embryo lethal for turkey poults and chicks and cause low hatchability. Culture methods have been known to be unreliable for monitoring M. iowae in natural infection due to intermittent spread and the unpredictable nature of this organism. in the present work M. iowae was isolated from vaginal and cloacal swabs of a naturally infected turkey hen. An immuno-gold light microscopy technique was utilized for identification of the organism in situ. The technique is being used to study the relationship between M. iowae and the tissues of the reproductive tracts of turkey. Photographs of the histology of infected turkey hen reproductive system are presented, as well as photographs of gold-labelled M. iowae microcolonies close to epithelial cell in tissues.